ADSORPTION CAPACITY OF ACTIVATED CHARCOAL FOR LANTHANIDES (III) IONS - Qadeer, R.; Saleem, M.; Khalid, N. (The Nucleus, 2010)
The adsorption of lanthanides metals namely Sm3+, Eu3+ and Gd3+ on activated charcoal has been studied as a function of pH at room temperature. Maximum adsorption was observed at pH value of 4. The adsorption mechanism has been described in term of hydrolysed species formed in aqueous solution at different pH. The adsorption of metal ions obeyed the Langmuir and Temkin isotherm models in the range of 1.0 to 6.0 g of metal ions per liter of solution. The values of adsorption capacities â€œQâ€ for Sm3+, Eu3+ and Gd3+ ions have been calculated at different pH. The adsorption capacities obtained from Langmuir model are in agreement with the determined values of Temkin constants â€œATâ€ from Temkin model. The determined adsorption capacities of the investigated metal ions varied in the order of Gd3+ > Eu3+ > Sm3+ ions and were correlated with the charge density (Z/r) of the metal ions studied.